The Influence Of The Principal's Participative Leadership Style And School Climate On Teachers' Work Ethic In MAN 2 Mojokerto, East Java, Indonesia - Wahib, Abd. (International Journal of Educational Research & Social Sciences, 2023)
The aim of this research is to analyze the significant influence of the principal's participative leadership style and school climate on the work ethic of teachers at MAN 2 Mojokerto, East Java, Indonesia. The approach in this research is quantitative. The type of research used in this research is associative research. The population is all teachers at MAN 2 Mojokerto. The sample used was 105 respondents. The data collection techniques are questionnaires and documentation. Data analysis used multiple linear regression.The results of the research areThere is a significant influence of the principal's participative leadership style on the teacher's work ethic, which means that the higher the participative leadership style, the higher the teacher's work ethic.;there is a significant influence of school climate on teacher work ethic, which means that the higher the school climate, the higher the teacher's work ethic; There is a significant influence of the principal's participative leadership style and the school climate on the teacher's work ethic, which means that the higher the principal's participative leadership style and the higher the school climate, the higher the teacher's work ethic.